COVID-19 in Patients with Multiple Sclerosis: Associations with Disease-Modifying Therapies - Reder, Anthony T.; Centonze, Diego; Naylor, Maria L.; Nagpal, Anjali; Rajbhandari, Rajani; Altincatal, Arman; Kim, Michelle; Berdofe, Aaron; Radhakrishnan, Maha; Jung, Eunice; Sandrock, Alfred W.; Smirnakis, Karen; et al. (CNS drugs, 2021)
Background Disease-modifying therapies (DMTs) for multiple sclerosis (MS) target immunity and have the potential to increase the risk of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection and alter its clinical course. We assessed these risks in patients with MS (PwMS). Objective The objective of this study was to describe the overall risk of coronavirus disease 2019 (COVID-19) infection, severe disease course, and potential population-level predictors of COVID-19 infection in PwMS, and to provide a context using a cohort of patients with systemic lupus erythematosus (SLE). In addition, the association of different MS DMTs with the incidence and clinical course of COVID-19 was evaluated. Safety data from the Biogen Global Safety Database are also presented on reported cases of COVID-19 in patients treated with Biogen MS therapies. Methods The IBM ® Explorys electronic health record database of > 72,000,000 patients from US healthcare networks identified patients with MS or SLE, with and without polymerase chain reaction-confirmed COVID-19. COVID-19 cumulative incidence, hospitalization, and deaths among DMT classes were compared using logistic regression (adjusted for age, sex, body mass index, comorbidities, and race/ethnicity). As a secondary data source to assess safety data, COVID-19 reports for Biogen MS therapies were extracted and described from Biogen’s Global Safety Database. Results 30,478 PwMS with an open DMT prescription were identified within Explorys; 344 were COVID-19 positive. The most significant risk factors for acquiring COVID-19 were comorbidity score ≥ 1, body mass index ≥ 30, and Black/African ancestry. Similar risk factors were also identified for patients with SLE. Patients with MS were less likely to develop COVID-19 when treated with interferons (0.61%) and glatiramer acetate (0.51%), vs all other MS DMTs (both p < 0.001); anti-CD20 therapy was associated with the highest risk (3.45%; p < 0.0001). In the Biogen Global Safety Database, we identified 1217 patients who were COVID-19 positive treated with intramuscular interferon beta-1a, peginterferon beta-1a, natalizumab, dimethyl fumarate, diroximel fumarate, or fampridine. Conclusions Comorbidities, obesity, and Black/African ancestry, but not age, were associated with a higher risk of SARS-CoV-2 infection in PwMS. Interferons and glatiramer acetate were associated with a reduced COVID-19 risk, whereas anti-CD20 therapies were associated with an increased risk, within the treated MS cohort. COVID-19 safety reports for patients receiving Biogen MS therapies were consistent with the Explorys database and MS literature, illustrating the replicability and power of this approach.